A atuação do Conselho Municipal dos Direitos da Criança e do Adolescente na região administrativa de Ivaiporã-PR frente à doutrina da proteção integral - Avanzi, Paula Fernanda (2018)
This dissertation aims to analyze the role played by the Municipal Councils of the Rights of the Child and Adolescent in the administrative region of Ivaiporã-PR, seeking to understand the difficulties, limits and possibilities within its scope, with the purpose of identifying whether these spaces carry out their actions in accordance with the Integral Protection Doctrine established by the Statue of the Child and Adolescent and if, in fact, they can guarantee the rights of the public in question or if the action still finds limits to break with standards conservative, considering the cultural marks that historically permeates public spaces, arising from Brazilian socio historical formation. The study was carried out from a bibliographical review of materials to the thematic of the study for the construction of the theoretical reference. In order to approach the universe of the study with the Rights of the Child and Adolescent of the cities of Ivaiporã, Lunardelli and São João do Ivaí and the subjects of the research, three municipal councilors of each council, we use as instrument of data collection semi-structured interviews and participant observation at council meetings, as well as documentary research, analyzing the minutes of the last three council meetings. The result of the research revealed that despite the normative advances and the advanced legislation that we have, the council‟s action still finds limits to break with conservative and centralizing decision make standards, thus, they do not guarantee Integral Protection for children and adolescents. However, we note that there are structured and conjectural issues that reverberate in the councils and corroborate so that these spaces still encounter difficulties and challenges in the scope of their action, therefore the councils still lack investments